Packaging Training for Traditional Emping Melinjo Crackers’ Producers in Menes Village, Pandeglang Banten - Marta Sanjaya (Social Economics and Ecology International Journal (SEEIJ), 2021)
Menes village in Pandeglang, Banten has long been known as the largest Emping Melinjo cracker producing area in Indonesia. The production process is carried out using a conventional process with family management, where each head of the family produces small to medium quantities of the cracker and then the middlemen or wholesalers collects them. The Emping producer’s community has some limitation in packaging knowledge and technology that makes them receive only a small profit. We provide a material regarding the good packaging concept to improve the knowledge of community. In addition, the booklet material also equipped with various explanations about marketing strategies to help the community develop products and increase sales. After receiving the booklet material, some feedbacks from participants gathered to find the effectiveness of such method of knowledge delivering.